Penerapan Sistem Dry Lot Fattening Dalam Manajemen Penggemukan Sapi Di Desa Jatirejo Kecamatan Loceret Nganjuk - Diyah Ayu Candra; Rico Anggriawan (Hikamatzu | Journal of Multidisciplinary, 2024)
The purpose of this study was to analyze the application of the dry lot fattening system in the management of cattle fattening in Jatirejo Village, Loceret Nganjuk District. The method used in this study was descriptive qualitative. how to collect qualitative data through observation, interviews, or study of documents. Data analysis with the theory of Miles and Huberman. research results Cattle fattening system using the dry lot fattening method can be implemented effectively in Jatirejo Village, Loceret District, Nganjuk. the application of the dry lot fattening system in the management of cattle fattening in Jatirejo Village, Loceret District, Nganjuk can be a solution to increase cattle production and beef quality. However, it is necessary to pay attention to important aspects such as providing adequate and quality feed, cleanliness of the stables, and the health of the cows to achieve optimal results.